2014
DOI: 10.1002/dvdy.24102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular ATIP (Angiotensin receptor type 2 interacting protein) expression in mouse development

Abstract: Background: ATIPs (Angiotensin receptor type 2 [AT2] interacting proteins) are described as AT2 interacting protein variants, whereas their expression and functions during development are not known yet. Results: Here, we provide a detailed expression pattern of ATIP variants during mouse development by visualizing Mtus1 promotor activity, Mtus1 RNA, and subsequent ATIP protein expression. ATIPs are strongly expressed in the developing cardiovascular system, including the vascular plexus of the yolk sac and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We previously have identified that MTUS1 isoform 5 is the major isoform in ECs (16). Previous studies showed that the MTUS1 was strongly expressed in the mouse developing cardiovascular system, including the vascular plexus of the yolk sac (22), suggesting that MTUS1 may be involved in the neovascularization. Here, we first evaluated the expression level of MTUS1 in ECs cultured within 2-dimensional collagen type I and 3-dimensional Matrigel.…”
Section: Mtus1 Silencing Inhibits Endothelial Tube Formation and Migrmentioning
confidence: 97%
“…We previously have identified that MTUS1 isoform 5 is the major isoform in ECs (16). Previous studies showed that the MTUS1 was strongly expressed in the mouse developing cardiovascular system, including the vascular plexus of the yolk sac (22), suggesting that MTUS1 may be involved in the neovascularization. Here, we first evaluated the expression level of MTUS1 in ECs cultured within 2-dimensional collagen type I and 3-dimensional Matrigel.…”
Section: Mtus1 Silencing Inhibits Endothelial Tube Formation and Migrmentioning
confidence: 97%
“…Total RNA of murine ES cells or EBs was extracted by using the peqGOLD RNAPure TM kit (Peqlab, Wilmington, DE). cDNA synthesis and PCRs were accomplished as described previously in (Bundschu and Schuh, ). Comparable cDNA amounts were adjusted according to the Gapdh expression levels.…”
Section: Methodsmentioning
confidence: 99%